Early onset of senescence and imbalanced epidermal homeostasis across the decades in photoexposed human skin: Fingerprints of inflammaging. Issue 11 (7th August 2022) - Jarrold, Bradley B.; Tan, Christina Yan Ru; Ho, Chin Yee; Soon, Ai Ling; Lam, TuKiet T.; Yang, Xiaojing; Nguyen, Calvin; Guo, Wei; Chew, Yap Ching; DeAngelis, Yvonne M.; Costello, Lydia; De Los Santos Gomez, Paola; et al.
Abstract: Inflammaging is a theory of ageing which purports that low‐level chronic inflammation leads to cellular dysfunction and premature ageing of surrounding tissue. Skin is susceptible to inflammaging because it is the first line of defence from the environment, particularly solar radiation. To better understand the impact of ageing and photoexposure on epidermal biology, we performed a system biology‐based analysis of photoexposed face and arm, and photoprotected buttock sites, from women between the ages of 20s to 70s. Biopsies were analysed by histology, transcriptomics, and proteomics and skin surface biomarkers collected from tape strips. We identified morphological changes with age of epidermal thinning, rete ridge pathlength loss and stratum corneum thickening. The SASP biomarkers IL‐8 and IL‐1RA/IL1‐α were consistently elevated in face across age and cis/trans ‐urocanic acid were elevated in arms and face with age. In older arms, the DNA damage response biomarker 53BP1 showed higher puncti numbers in basal layers and epigenetic ageing were accelerated. Genes associated with differentiation and senescence showed increasing expression in the 30s whereas genes associated with hypoxia and glycolysis increased in the 50's. Proteomics comparing 60's vs 20's confirmed elevated levels of differentiation and glycolytic‐related proteins. Representative immunostaining for proteins of differentiation, senescence and oxygen sensing/hypoxia showed similar relationships. This system biology‐based analysis provides a body of evidence that young photoexposed skin is undergoing inflammaging. We propose the presence of chronic inflammation in young skin contributes to an imbalance of epidermal homeostasis that leads to a prematurely aged appearance during later life. Abstract : A heightened inflamed state remains constant across the decades in the epidermis of photoexposed facial skin whereas underlying processes such as differentiation, senescence, oxygen sensing/hypoxia, epigenetic drift and metabolic reprogramming steadily increase. In contrast, epidermal proliferation declines with age. These suggest that inflammaging in skin leads to an imbalance in epidermal homeostasis with photoaging.